2015
DOI: 10.3928/01477447-20150402-06
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Prophylaxis After Total Joint Arthroplasty

Abstract: Venous thromboembolism (VTE) prophylaxis after total joint arthroplasty is considered best practice. However, over the past 5 years, there has been considerable debate about the ideal prophylactic regimen or modality. The American Academy of Orthopaedic Surgeons and the American College of Chest Physicians published their most recent clinical practice guidelines about VTE prophylaxis in 2011 and 2012, respectively. In addition, the Surgical Care Improvement Project published their latest recommendations in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…[32][33][34][35][36] Incidences of clinically relevant symptomatic VTE after hip and knee arthroplasty have also been reported in East Asian populations. 30,31 In a systemic review and meta-analysis, Kanchanabat et al 5 examined the incidence of VTE after orthopedic surgery in Asian patients without thromboprophylaxis and found very low incidence of proximal and symptomatic DVT as compared to Western populations, and no patient died of DVT. 35 Interracial differences, genetic factors, and a Western lifestyle may affect the occurrence of DVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35][36] Incidences of clinically relevant symptomatic VTE after hip and knee arthroplasty have also been reported in East Asian populations. 30,31 In a systemic review and meta-analysis, Kanchanabat et al 5 examined the incidence of VTE after orthopedic surgery in Asian patients without thromboprophylaxis and found very low incidence of proximal and symptomatic DVT as compared to Western populations, and no patient died of DVT. 35 Interracial differences, genetic factors, and a Western lifestyle may affect the occurrence of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Without DVT prophylaxis, this procedure is associated with high DVT and PE risk of up to 85%, which necessitates VTE prophylaxis. 5 Patients who develop VTE are faced with about 10times higher healthcare costs and hospital stays of more than twice the length of patients who do not develop VTE. The mortality rate after PE is 19.49%.…”
Section: Introductionmentioning
confidence: 99%
“…Their use and efficacy following joint arthroplasty has been well documented, but the efficacy of such devices for VTE prevention is less well accepted after spine surgery. 8,9 Rokito et al 10 reported a prospective evaluation of the incidence of DVT after elective adult spine surgery. A total of 329 patients in total were included and randomized to 1 of 3 groups.…”
Section: External Compression Devicesmentioning
confidence: 99%
“…The VTE prevention guidelines by the American Academy of Orthopedic Surgeons (AAOS) or the American College of Chest Physicians (AACP) have been implemented in most countries in Asia [ 2 , 3 ]. However, there are some concerning issues and complications related to VTE prophylaxis in major joint replacement and hip fracture surgeries according to these guidelines, due to differences in the healthcare systems and various cultural aspects [ 4 6 ].…”
mentioning
confidence: 99%